, ...compared to my narrow value, I should set an example for those who are more wealthy...’’ The career and foundation of László Géressy (1804–1870), a reformed pastor of Visk. - Becske, Pál Zsolt (Church History Review, 2025)
This study presents the life and work of a 19th-century Reformed pastor from Máramaros. László Géressy, who came from an ancient Reformed clerical family, was one of the prominent and influential figures of his time. Relatively little is known about his life and foundation; a detailed account of his career and diverse activities has not been presented until now. László Géressy, who also had noble ancestors, was born 1804 in Beregrákos (Bereg County). He began his studies at the school of Beregrákos and then became a student at the Reformed College of Sárospatak. After completing his higher education, he accepted a pastoral post in Csepe. Between 1832 and 1834, he served as a pastor in Forgolány. Then, in 1834, at the invitation of the local Reformed congregation, he moved to Visk. In the former crown city of Máramaros, he served as a pastor for nearly thirty-six years. Géressy’s ecclesiastical and public activities were undoubtedly epoch-making. The peak of his work came in the period following the Hungarian revolution and war of independence of 1848–49, but he had already made lasting contributions in several areas before. Besides developing the infrastructure of the parish, Géressy played an important role in advancing local public education conditions. Among other things, he is credited with organizing the local Civic Reading Circle and establishing the Sunday school. He also wrote several historical handbooks and articles, and he actively participated in the anti-alcohol movement. Perhaps one of his most significant achievements was the establishment of the School Foundation on January 1, 1840, which played a crucial role in improving local Reformed educational conditions and supporting those in need.